Informalidade brasileira: o fenômeno tem rosto feminino? Uma análise para o período 2012-2019 - Oliveira, Bárbara Raquel de (2022)
The objective of this work is to investigate the current behavior of the Brazilian informal labor market to identify whether as an objective they fit the role of the portion most affected by the aspects of this sector. A hypothesis as explained, which is a good possibility of the informal labor market, a larger woman who is inserted, a measure that is a participation variable that influences the differences in the probability of participation in occupations. To achieve the proposed objectives, the study methodology involves carrying out a review of literature, as the main theoretical currents of informality. In addition, the study brings a descriptive research based on the Continuous National Household Sample Survey (PNADC) for the years 2012 and 2019 and ends with the execution of the Probit econometric model, based on microdata also from PNADC to The year 2019. The main results show that, as women in the field of probabilities, women are more likely to be inserted in informality, that is, even if they have not had a formal contract and are not a social security contributor and have not yet to be a social security contributor Both sexes in relation to the total proportion of similar sexes in the observed years of work data, one of them surpasses that of men in relation to years of age and the most precarious working conditions in relation to the position in informal occupation.